Withdrawal from Long-Term Use of Unusually High-Dose Oxazepam - Mustonen, Antti; Leijala, Juhani; Aronranta, Johanna; Lassila, Antero; Aalto, Mauri; Koskimäki, Janne (Case Reports in Psychiatry, 2021)
Benzodiazepine (BZD) misuse is a worldwide problem that healthcare professionals encounter in daily practice. High-dose BZD withdrawal is usually a long process that may require referral to an inpatient rehabilitation unit. Relapses after withdrawal are common. BZD withdrawal can cause complications including seizures, suicidal behavior, anxiety, and depression. Guidelines describe tapering protocols for modest doses; however, protocols for exceptionally high-dose BZD withdrawal are not well described. Herein, we describe a BZD tapering protocol for a patient with daily use of high-dose (1800 mg) oxazepam (OXP). The BZD tapering was administered in an inpatient psychiatric hospital, and the outcome was evaluated monthly after discharge for three months. This report describes a unique case of high-dose OXP withdrawal and also outlines an optional protocol to apply when clinicians encounter these unusual cases.